Gestión financiera y nivel de endeudamiento en comerciantes del centro ferial Sachachorro, Iquitos; periodo 2024 - Alvarez López, Dianelis de la Caridad (2024)
The objective of this research was to evaluate the relationship between financial management and the level of indebtedness of the merchants of the Sachachorro Fair Center, Iquitos, during the year 2024; With a type of quantitative research of correlational scope, of non-experimental design and type of cross-sectional design, the study population included 185 merchants who operate in the Sachachorro Fair Center, Iquitos; The research concluded that the correlation coefficient of 0.107 for the variable Financial management practices and Level of debt indicates a weak positive correlation between these two variables, indicating that as financial management practices improve, the level tends to increase. of indebtedness; Furthermore, the significance value (0.147) suggests that this correlation is not statistically significant at a typical 95% confidence level, as the p-value is greater than 0.05. In summary, based on these results, there does not seem to be a significant relationship between financial management practices and the level of debt, rejecting the null hypothesis and accepting the alternative.